Melhorias no projeto de interface como resultado de avaliações formativas de IHC: o caso de um Sistema Jurídico - Santos, Rafael Dias (2020)
Evaluation is an important activity during solution design. Although there are specific evaluation methods for digital design, little is investigated about their effects on design process. This work presents a case study which analyzed the use of formative evaluation results with heuristic evaluation, communicability evaluation method and usability test on the review of solution being designed. Evaluation contributions have been pointed out and questions about solution review need to further research.